Ensam fras söker kontext: Översättarens hantering av språkprov i en tvåspråkig ordbok - Hellerud, Ylva (Nordiske Studier i Leksikografi, 2012)
Working as a translator for the inter-Scandinavian dictionary project Islex, presents a number of interesting challenges due to the fact that the source language material is compiled and presented based on a monolinguistic semantic analysis. In this article I describe the process involved in choosing the most relevant translations of the examples provided for the lemmas rekstrarerfiðleikar and veðrast, focusing on the problem of lack of context. Finally I discuss the possibilities made available by digital publishing on the world wide web.